Pedagogical approaches to the development of artistic thinking of students. (International conference on multidisciplinary science, 2023)
The article highlights the problems in the development of artistic and figurative thinking, the researchers who contributed to the research and understanding of the development process of artistic and figurative thinking and had a great influence on the theory and practice of education around the world.